2013
DOI: 10.2478/s13382-013-0099-x
|View full text |Cite
|
Sign up to set email alerts
|

Exposure to widespread environmental toxicants and children’s cognitive development and behavioral problems

Abstract: Nowadays a special attention is focused on prenatal and childhood exposures to a variety of contaminants in the environment, especially toxicants widely present in the environment and their impact on children's health and neurodevelopment. This article aims at evaluating the impact of exposure to several widespread toxicants including: polycyclic aromatic hydrocarbons (PAHs), phthalates, bisphenol A, brominated flame retardants and gas cooking on children's cognitive development and behavioral problems by revi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(24 citation statements)
references
References 66 publications
0
23
0
Order By: Relevance
“…These include persistent organic pollutants (POPs) – polychlorinated bipehenyls (PCBs) (Kodavanti 2005; Gascon et al, 2013; Faroon et al, 2001; Buters et al, 2007; Fitzgerald et al, 2012; Chia & Chu, 1984); organochlorine pesticides (OCs) (Jurewicz et al, 2013b; Moses et al, 2010; Iwaniuk et al, 2006; Colosio et al, 2003; Lee et al, 2008b); dioxins and furans (Kodavanti 2005), and polybrominated biphenyl ethers (PBDEs) used as fire retardants (Kodavanti 2005; Buters et al, 2007; Fitzgerald et al, 2012; Widholm et al, 2003; Thomke et al, 1999; Michalek et al, 2001; Sweeney et al, 1993); BPA, widely used in the manufacture of plastic food containers and other applications (Viberg et al, 2011; White et al, 1997; Viberg et al, 2012; Yolton 2011); phthalates, widely used as plasticizers for polyvinyl chloride (Jurewicz et al, 2013a; Le Cann et al, 2011; Yolton et al, 2011), which are exuded from plastics; low molecular weight aliphatic and aromatic hydrocarbons (LMWHCs) and their chlorinated products which evaporate from gasoline, adhesives, paints and household products (Viaene, 2002; Maruff et al, 1998; Burbacher, 1993; ATSDR, 2001; Lammers et al, 2011); and polynuclear aromatic hydrocarbons (PAHs) which come from primary and secondary tobacco smoke inhalation and fuel combustion (ATSDR, 1995; He et al, 2012; Patri et al, 2009; Krivoshto et al, 2008). …”
Section: Resultsmentioning
confidence: 99%
“…These include persistent organic pollutants (POPs) – polychlorinated bipehenyls (PCBs) (Kodavanti 2005; Gascon et al, 2013; Faroon et al, 2001; Buters et al, 2007; Fitzgerald et al, 2012; Chia & Chu, 1984); organochlorine pesticides (OCs) (Jurewicz et al, 2013b; Moses et al, 2010; Iwaniuk et al, 2006; Colosio et al, 2003; Lee et al, 2008b); dioxins and furans (Kodavanti 2005), and polybrominated biphenyl ethers (PBDEs) used as fire retardants (Kodavanti 2005; Buters et al, 2007; Fitzgerald et al, 2012; Widholm et al, 2003; Thomke et al, 1999; Michalek et al, 2001; Sweeney et al, 1993); BPA, widely used in the manufacture of plastic food containers and other applications (Viberg et al, 2011; White et al, 1997; Viberg et al, 2012; Yolton 2011); phthalates, widely used as plasticizers for polyvinyl chloride (Jurewicz et al, 2013a; Le Cann et al, 2011; Yolton et al, 2011), which are exuded from plastics; low molecular weight aliphatic and aromatic hydrocarbons (LMWHCs) and their chlorinated products which evaporate from gasoline, adhesives, paints and household products (Viaene, 2002; Maruff et al, 1998; Burbacher, 1993; ATSDR, 2001; Lammers et al, 2011); and polynuclear aromatic hydrocarbons (PAHs) which come from primary and secondary tobacco smoke inhalation and fuel combustion (ATSDR, 1995; He et al, 2012; Patri et al, 2009; Krivoshto et al, 2008). …”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, introduction of regulations to prevent potential contaminations is essential. Due to the increased vulnerability of infants, the determination of toxic contaminant levels in breast milk is important [61][62][63].…”
Section: Discussionmentioning
confidence: 99%
“…The exact cause of delayed cognitive development in children is still uncertain but its etiology is likely to be complex and may be caused by multifactorial interactions. Previous studies have found several risk factors for delayed cognitive function in children, such as low parental literacy, maternal smoking during pregnancy, and exposure to environmental toxicants [3][4][5][6]. Thyroid hormones play a major role in the neurodevelopment of fetuses, infants, and children [7][8][9].…”
Section: Introductionmentioning
confidence: 99%